Characterization of pediatric patients with melanocytic nevi - Damarys Díaz Leonard; Leonel Díaz Arjones; Marlene Curbelo Alonso; Mery Rosa Betancourt Trujillo; Lino A. Sánchez Galván (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Foundation: Melanocytic nevi are very common benign skin lesions found in the entire population. They are proliferations derived from melanocytes, the cells responsible for normal skin pigmentation. Objective: to characterize pediatric patients with melanocytic nevi. Methods: descriptive study of case series. All patients (N = 174) with melanocytic nevi (N = 194) who attended the specialized clinic of the Paquito González Cueto Pediatric Hospital were studied in the period from November 2013 to November 2014. Some information was taken from the medical records. Clinical and dermatoscopic diagnosis of nevi was performed. To classify the lesions according to the degree of malignancy, the total dermatoscopic index was applied. Results: nine-year-old patients predominated, as well as female and white skin. 74% of the patients had a family history of nevi. The acquired nevi were the most frequent (44.2%), followed by the congenital ones (42.5%). Results: nine-year-old patients, as well as female and white skin, predominated. In the dermatoscopy score benign nevi was predominant with 90.7%. In 29.4% of the biopsies indicated, the clinical and histological diagnosis did not correspond. Conclusion: in pediatric patients, it is important to monitor the appearance of nevi mainly at ages close to puberty, and in children with white skin. Both the clinical and the dermatoscopy diagnosis are important, but the histological study is essential when there is suspicion of malignant lesions or with the trend to be malignant.